Assessing the effectiveness of upper-limb spasticity management using a structured approach to goal-setting and outcome measurement: First cycle results from the ULIS-III Study - Lynne Turner-Stokes; Jorge Jacinto; Klemens Fheodoroff; Allison Brashear; Pascal Maisonobe; Andreas Lysandropoulos; Stephen Ashford (Medical Journals Sweden, 2021)
Objective: To describe the utility of a structured approach to assessing effectiveness following injection with botulinum toxin-A alongside physical therapies, within the first cycle of the Upper Limb International Spasticity-III (ULIS-III) study. Methods: ULIS-III (registered at clinicaltrials.gov as NCT02454803) is a large international, observation-al, longitudinal study of adults treated for upper-limb spasticity. It introduces novel methods for the structured evaluation of person-centred goal attainment alongside targeted standardized outcome measures: the Upper limb Spasticity Index, and the Upper Limb Spasticity Therapy Recording Schedule. Results: A total of 953/1,004 enrolled patients (95%) completed cycle 1. Mean overall goal attainment scaling (GAS) T scores were 49.8 (95% confidence interval 49.2-50.3; 67.1% of patients met their primary goal, with highest achievement rates for goals related to involuntary movement, (75.6%) and range of movement (74.4%). Standardized measures of spasticity, pain, involuntary movements, active and passive function, all improved significantly over the treatment cycle. Overall, 59.7% of patients saw a therapist following botulinum toxin-A injection. Interventions varied, as expected, with the set treatment goals. After controlling for concomitant therapies using the upper limb spasticity therapy recording schedule, significant differences in injection intervals (p <  0.001) were seen between the commercially-available botulinum toxin-A agents. Conclusion: The results of this study confirm the utility of the Upper Limb Spasticity Index and Upper Limb Spasticity Therapy Recording Schedule as a structured approach to capturing goal-setting, therapy inputs and outcomes assessment.